Approaches to the Violence Against Women in the Recent Narrative Fiction from Latino America - Navarrete-Barria, S (UNIV PITTSBURGH, UNIV LIBRARY SYSTEM, 2023)
This study proposes a panoramic approach to the recents narratives that represent the theme of violence against women s bodies. To this end, we will focused on a group of novels from Mexico, Colombia, Chile and Argentina that address this issue from different thematic angles and aesthetic nuances. This corpus allowed us to work the following hypothesis: the recent narrative fictions that draw up the violence against women configure an innovative interpretative framework of interpretation about this issue that lay out and expand the ways of understood the violence. Our main aim is to explore and analize the different ways in which these narratives weave a reformulation of the meaning of gender violence, in our current Latin American context.